Membangun Literasi Digital Peserta Didik melalui Pendidikan Kewarganegaraan di Era Globalisasi Media Sosial - Pertiwi, Ananda; Pramudika, Natalen Risky; Isnaini, Pajri; Fikri, Raka AIdil (Indonesian Journal of Law and Justice, 2025)
The rapid development of technology in the era of globalization has positioned social media as the main space of interaction for young generations. On the one hand, social media provides vast opportunities for learning and civic participation; on the other hand, it also brings serious challenges such as weak digital literacy, the prevalence of cyberbullying, hate speech, and disinformation. This study aims to explore the role of Civic Education in fostering students’ digital literacy so that they can become intelligent and civilized digital citizens. The research employs a descriptive qualitative method based on a literature review of scholarly works related to Civic Education, digital literacy, and digital citizenship. The findings indicate that Civic Education plays a crucial role in: (1) strengthening Pancasila values as moral foundations, (2) enhancing critical digital literacy to counter hoaxes and disinformation, (3) shaping responsible digital citizenship, and (4) promoting synergy among schools, families, and communities in cultivating ethical media practices. These results highlight that strengthening Civic Education in the digital era is a strategic step to form students who are intelligent, critical, and civilized amidst the dynamics of globalization.